d-Gaussian Fibonacci, d-Gaussian Lucas polynomials and their matrix representations - Özkan, E.; Uysal, M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5 We define d-Gaussian Fibonacci polynomials and d-Gaussian Lucas polynomials. We present the matrix representations of these polynomials. By using the Riordan method, we obtain the factorizations of the Pascal matrix including the polynomials. In addition, we define the infinite d-Gaussian Fibonacci polynomial matrix and the d-Gaussian Lucas polynomial matrix and give their inverses.